Policy Enactment and Institutional Readiness for Artificial Intelligence in Ethiopian Higher Education: A Multilevel Analysis of Challenges and Capacity Gaps - Belay Sitotaw Goshu (Matondang Journal, 2027)
Ethiopia has emerged as a continental leader in artificial intelligence (AI) policy, establishing the Ethiopian Artificial Intelligence Institute (2020), approving a National AI Policy (2024), and committing US$324 million to the world's second AI-dedicated university (scheduled for 2027). However, the translation of this ambitious national vision into institutional practice within higher education remains critically under-examined. This study investigates AI policy enactment and institutional readiness across Ethiopian higher education institutions (HEIs), examining the alignment between national policy aspirations and implementation capacity at macro, meso, and micro levels. Drawing on Stephen Ball's Policy Enactment Framework, the study employed a qualitative multilevel case study design. Data were collected through policy document analysis, institutional records, semi-structured interviews with 400 stakeholders (policymakers, university administrators, faculty, and students), surveys of faculty AI literacy (N=376), and observational site visits across seven purposively selected Ethiopian public universities. Ethiopia has made significant policy advances, but a substantial readiness gap persists. Infrastructure limitations, particularly inadequate internet connectivity and computing resources, remain critical obstacles. Faculty AI literacy is limited, with only 35% reporting basic awareness and 8% competence in curriculum development. Institutional readiness varies considerably, with some universities demonstrating strategic vision while others lack coherent AI strategies. Cross-cutting challenges include weak governance structures, data privacy vulnerabilities, and institutional resistance to change. The successful integration of AI in Ethiopian higher education requires coordinated action across all levels of the education system. Without deliberate, equity-focused interventions, AI adoption risks exacerbating existing educational inequalities between urban and regional institutions. Policymakers should finalise the National AI Policy with clear implementation guidelines and allocate dedicated funding for existing universities. University administrators should develop institutional AI strategic plans, invest in ICT infrastructure, and establish innovation hubs. Faculty must participate in structured AI literacy programmes and integrate AI content across disciplines. Development partners should support infrastructure development and facilitate South-South cooperation on AI in education.